2018
DOI: 10.1038/sdata.2018.283
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and protein interaction profiling in cancer cells with mutations in histone H3.3

Abstract: Mutations of histone variant H3.3 are highly recurrent in childhood glioblastoma and in young adults with Giant Cell Tumor of the Bone (GCTB). The heterozygotic representation of the mutations in the tumors, and with potential histone H3 and H3.3 redundancy, suggest that the mutations are gain-of-function by nature. To address common H3.3 point mutations, we have generated data from GCTB patient samples with H3.3 G34W substitutions and engineered human GFP-tagged H3.3-mutated isogenic cell lines for high throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Numerous studies have reported connections between cancer and splicing, providing detailed insight into the accumulation of aberrant splice variants [2]. In previous research, extensive RNA processing aberrations were described in giant cell tumor of bone (GCTB), which were linked to mutations in the histone variant H3.3 [3,4]. GCTB is a benign tumor, and over 90% of patients carry a mutation of the histone variant H3.3, resulting in the substitution of glycine 34 with tryptophan (H3.3-G34W).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported connections between cancer and splicing, providing detailed insight into the accumulation of aberrant splice variants [2]. In previous research, extensive RNA processing aberrations were described in giant cell tumor of bone (GCTB), which were linked to mutations in the histone variant H3.3 [3,4]. GCTB is a benign tumor, and over 90% of patients carry a mutation of the histone variant H3.3, resulting in the substitution of glycine 34 with tryptophan (H3.3-G34W).…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of histone variant H3.3 into chromatin, as well as its somatic missense mutations dramatically alter the epigenomic landscape and the gene expression profile of a cell. Previous studies suggested that distinct gene expression patterns (45), transcriptome and interactome profiles (46) are established between tumors carrying different H3.3 mutations. Therefore, H3.3 mutations in CNS cancers are considered both as disruptors of the expression of genes required for brain function and as drivers of tumorigenesis (44,46).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that distinct gene expression patterns (45), transcriptome and interactome profiles (46) are established between tumors carrying different H3.3 mutations. Therefore, H3.3 mutations in CNS cancers are considered both as disruptors of the expression of genes required for brain function and as drivers of tumorigenesis (44,46). In conclusion, histone variants play significant roles in epigenetic regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Rpp29-ko resulted in increased levels of H3K36me3. Lim et al did demonstrate that purified H3.3-G34R from isogenic HEK293 cells had an increased protein-protein interaction with HIST3H2A and HIST1H2AC [38], and Huang et al [30] demonstrated that H3.3-G34V co-enriches with H3.3-wt. Another possible explanation is that H3K36me3 levels are increased in other oncogenes, such as MYCN, balancing the decreased levels in cis [33,39].…”
Section: Histone H33-g34r/v Mutations Affect Post-translational Modif...mentioning
confidence: 99%
“…Additionally reported is the possibility of fusion genes such as CSGALNACT2:RET and DHX57:TMEM178:MAP4K3 [87]. Lim et al introduced the H3.3-G34R mutation to HEK293 and discovered that this mutation resulted in 20 unique interactions with proteins that were not observed in H3.3-wt, H3.3-G34W, or H3.3-K27M [38]. There is varying data on the frequency of co-occurring CDKN2A/2B mutations [62,64,67,75].…”
Section: Other Possible Key Proteins and Pathways Involved In Gliomag...mentioning
confidence: 99%